Universal Index Theorem on Möb(S1)∖Diff+(S1)Möb(S1)∖Diff+(S1) - TEO, L (ELSEVIER SCIENCE BV, 2008)
By conformal welding, there is a pair of univalent functions (f, g) associated to every point of the complex Kahler manifold Mob(S(1))\Diff(+)(S(1)). For every integer n >= 1, we generalize the definition of Faber polynomials to define some canonical bases of holomorphic (1 - n)-and n-differentials associated to the pair (f, g). Using these bases, we generalize the definition of Grunsky matrices to define matrices whose columns are the coefficients of the differentials with respect to standard bases of differentials on the unit disc and the exterior unit disc. We derive some identities among these matrices which are reminiscent of the Grunsky equality. By using these identities, we showed that we can define the Fredholm determinants of the period matrices of holomorphic n-differentials N(n), which are the Gram matrices of the canonical bases of holomorphic n-differentials with respect to the inner product given by the hyperbolic metric. Finally we proved that det N(n) = (det N(1))(6n2-6n+1) and partial derivative(partial derivative) over bar log der N(n) is - (6n(2) - 6n +1)/(6 pi i) of the Weil-Petersson symplectic form. (C) 2008 Elsevier B.V. All rights reserved.